Realization of a Laughlin state of two rapidly rotating fermions - Lunt, Philipp; Hill, Paul; Reiter, Johannes; Preiss, Philipp; Galka, Maciej; Jochim, Selim (Physical review letters, 2024)
We realize a Laughlin state of two rapidly rotating fermionic atoms in an optical tweezer. By utilizing a single atom and spin resolved imaging technique, we sample the Laughlin wave function thereby revealing its distinctive features, including a vortex distribution in the relative motion, correlations in the particles’ relative angle, and suppression of the interparticle interactions. Our Letter lays the foundation for atom-by-atom assembly of fractional quantum Hall states in rotating atomic gases.
Gesehen am 27.11.2025